Seroprevalence of Rubella in a Group of Moroccan Parturients and Physicians' Opinions - Kenza Hattoufi; Hassan Aguenaou; Aicha Kharbach; Amina Barkat (Mashhad University of Medical Sciences, 2022)
Background: Rubella is an acute viral disease generally mild in its clinical manifestations. However, it is most serious for pregnant women due to the high frequency of congenital abnormalities that it causes, known as congenital rubella syndrome. This study aimed to determine rubella seroprevalence among a group of Moroccan parturients and survey physicians' opinions regarding the situation of congenital rubella syndrome in different regions of Morocco.Methods: We prospectively enrolled 1500 women hospitalized in the Maternity Souissi of Rabat for delivery and 14 pediatricians/neonatologists who were practicing in public and private centers representing different regions of Morocco. Data on rubella serological status were extracted from the medical records of mothers. The physicians involved in this study were visited to answer the survey in person, or they completed the survey by e-mail or phone discussion.Results: Among enrolled women, and after excluding those who did not bring back evidence of a serological assessment, 222 (17.5%) women performed a rubella serology of which 84.7% were immunized against rubella. The opinion poll of physicians showed an almost absence of reports on congenital rubella syndrome cases. All practitioners surveyed were interested to join the establishment of congenital rubella syndrome reporting system.Conclusion: To achieve the goals set for congenital rubella syndrome elimination, it is of primary importance to protect women from the childbearing age by vaccination and measures that help avoid any further contact with the virus. There is also a need to expand serological screening to detect and monitor seronegative women. In addition, it is necessary to diagnose and notify new cases of congenital rubella syndrome.